Web and Android-Based Islamic Study Applications to Increase Community Knowledge - Krisnanta Ravi Cakra Kusuma; Tutik Khotimah; Hanik Hidayati (PT FORMOSA CENDEKIA GLOBAL, 2023)
Studying religious knowledge and practicing it is an obligation for all Muslims. With the development of information technology, people tend to rely on gadgets for everything, including seeking information related to religion. The Muslim community needs a video platform containing Islamic studies with detailed information on studies and preachers so that they can listen to and learn about Islamic studies easily. This study aims to produce an application program to make it easy for the general public to learn Islamic studies. The results of this study are the Application of Islamic Study Media to Improve Community Insights Web-Based and Android which is designed using the Waterfall method and the programming language Java, PHP and MySQL and is expected to be able to help the community and presenters of lectures in learning studies and also knowing study schedules so that they become more easy and convenient.